Kontribusi Dana Desa dalam Pembangunan Badan Usaha Milik Desa Di Desa Hanura, Kabupaten Pesawaran, Provinsi Lampung - Abdul Mutolib; Dewangga Nikmatullah; Irwan Effendi (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2019)
One of the government's efforts to accelerate development in disadvantaged, deepest and outermost regions is through the Village Fund Policy. One of the obligations after the issuance of Law No. 6 of 2014 is the implementation of BUMDes (Village-Owned Enterprises). The study aims to analyze the contribution of Village Funds in the development of BUMDes in Hanura Village, Teluk Pandan District, Pesawaran District, Lampung Province. The study used a qualitative descriptive approach. Data collection was carried out through in-depth interviews with village officials and managers of BUMDes and field observations. The results of this study indicate that village funds in Hanura Village have contributed to the development of BUMDes. In 2018 the Hanura Village Government budgeted costs for the Procurement of Infrastructure Production Activities for Agriculture / livestock / fisheries production of Rp. 12,265,000.00. Then the Budget for Procurement of Marketing Infrastructure Activities (Shop and Cooperative Development) is Rp. 104,700,000.00, and the Community Economic Business Development and Establishment Activities (for other Capital Equipment and Machine Expenditures and animal and livestock capital expenditures) of Rp. 39,999,997.00. The business units owned by BUMDes Conscience include: 1) Market Management, 2) Product and Service Units, 3) Home Industry. One of the BUMDes marketing strategies is through online sales through the BUMDes website.